Beneficial Effects of Silybin Treatment After Viral Eradication in Patients With HCV-Related Advanced Chronic Liver Disease: A Pilot Study - Cossiga, Valentina; Sanduzzi-Zamparelli, Marco; Sapena, Victor; Guarino, Maria; Dallio, Marcello; Torrisi, Emanuele; Pignata, Luca; Federico, Alessandro; Salomone, Federico; Morisco, Filomena (Frontiers in Pharmacology, 2022)
Introduction and Aims: HCV eradication by direct-acting antiviral agents (DAA) improves liver outcomes and reduces overall liver mortality. However, patients with advanced chronic liver disease (ACLD) may experience a progression of liver disease despite viral clearance. Silybin has shown hepatoprotective effects in experimental models, but clinical data are limited. The aim of this study is to evaluate the effect of a highly bioavailable form of silybin on liver fibrosis in patients with HCV-related ACLD after viral eradication with DAAs, in comparison to standard of care. Methods: In this multicenter and prospective study, HCV patients with ACLD achieving SVR12, were treated with the combination of silybinphospholipid complex with vitamin D and vitamin E (Realsil 100D®, Ibi Lorenzini S.p.A., Aprilia, Italy) for 12 months (R group) compared to controls (C group). Patients were submitted to Transient Elastography (TE) and to Enhanced Liver Fibrosis (ELF) test at baseline, week 24 and week 48. Results: One-hundred-sixteen patients were enrolled, 56 in the R group and 60 in the C group. The median age was 68 years and 53% were males, with no differences between groups. In both groups, liver stiffness improved at 6 and 12 months compared to baseline. However, patients in the R group compared to those in the C group showed a higher reduction of liver stiffness after 6 months (-2.05, %CI -3.89 to -0.22, p < 0.05) and 12 months of treatment (-2.79, %CI -4.5 - to -1.09, p < 0.01) in comparison to baseline. No significant difference in the reduction of ELF were observed between the two groups. During the follow-up, 4 patients developed HCC, all in the C group. Conclusions: In HCV-related ACLD, the hepatoprotective effects of silybin may represent a tool to counteract liver disease progression.